Pengembangan Media Pembelajaran Poster LKPD (POLKA PD) Model ADDIE untuk Meningkatkan Kemampuan Pemahaman Matematis Siswa - Rahayu, Ika Sri; Zaenal, Reza Muhamad; Yusritawati, Ita (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to design and determine the feasibility and effectiveness of LKPD Poster Learning Media (POLKA PD) to improve students' mathematical understanding, especially in flat-sided geometric material. This research uses Research and Development (R&D) research with the ADDIE development model and research design using one group pretest-posttest design. The population of this study only consisted of class VIII students at MTs Negeri 3 Kuningan for the 2023/2024 academic year. The sampling technique used in this research was simple random sampling. From the research results, it was found that the POLKA PD media developed was suitable for use in educational environments, based on the verification results of media experts and material experts. The POLKA PD media developed is effective in increasing students' mathematical understanding. This can be seen from the average student mathematics comprehension test score after using POLKA PD media which is higher than before. The development of POLKA PD media on flat-sided geometric material received a good response from students. This can be seen from the results of a survey of student responses to POLKA PD media